Rights Respecting Justice for Children in Conflict with the Law: Briefing Paper from the Rights Respecting Group in the UK, Jersey and Ireland - Anthony Charles (2024)
This paper provides an overview of discussions within the Rights Respecting Group from May2021 - September 2023. This group was represented by academics and campaigners workingin the field of children’s rights within the six nations of England, Ireland, Jersey, NorthernIreland, Scotland and Wales. This paper aims to highlight the most pressing concerns forchildren’s rights across the nations, highlighting the similarities and differences in policy andpractice.